Reliability Analysis of Sakarya Area Electricity Distribution System - Adem Taşın; Türker Fedai Çavuş (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Power system reliability is an important issue for providing minimal loss of service to each user. It is accepted that almost 90% of power outages are caused by failures in the Electricity Distribution System. In this study, the reliability analysis of the Alancuma feeder belonging to the Sakarya distribution system was aimed. The reliability assessment of the feeder was made using the analytical approach, Monte Carlo simulation (MCS) technique and ETAP (Electrical Transient and Analysis Program) software, and the results were observed to be close to each other. The most commonly used SAIFI and SAIDI system indices were evaluated according to the Turkey average and the reasons for the interruption for the feeder were investigated.